TINJAUAN FILSAFAT MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM PEMBELAJARAN BAHASA INDONESIA - Rani Setiawaty; Fitri Wahyuningtiyas; Diva Aulia Zahra; Dwi Amelia Noor; Meidheana Putri Fatikasari; Fareel Aby Firnandi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
The purpose of this study is to identify Indonesian language learning through the Project Based Learning (PjBL) learning model reviewed from the perspective of ontology, epistemology, and axiology. The research method used is the Systematic Literature Review (SLR) method. The data for this study used 20 articles collected through Google Scholar and the Publish or Perish (POP) application. Data analysis was carried out in depth to draw conclusions. Based on the results of the analysis, it was concluded that the ontology of the Project Based Learning (PjBL) learning model is an innovative approach that positions learners as active subjects in constructing knowledge through group collaboration and the completion of teacher-designed projects. The epistemology of the Project Based Learning (PjBL) learning model in learning Indonesian can be done through several steps, (1) Determining the project, (2) Designing project completion steps, (3) Preparing a project implementation schedule, (4) Completing the project with teacher facilitation and monitoring, (5) Preparing reports and presentations/project publications, (6) Evaluating the process and results of the project. Meanwhile, the axiology of the PjBL model provides a positive influence and increases learning activities in learning Indonesian. More specifically, literature findings indicate that PjBL enhances students’ motivation, increases active participation, improves collaboration in group tasks, and strengthens higher-order thinking skills, particularly in activities such as text analysis, writing projects, and digital-based presentations.